Drosophila memory: dopamine signals punishment? - Keene, A; Waddell, S (2005)
Dopamine-containing neurons are widespread in the fly brain and have been implicated in negatively reinforced memory. Current technology allows the investigator to watch dopaminergic neurons in action in the brain of a learning fly.